2006
DOI: 10.1103/physrevb.73.235353
|View full text |Cite
|
Sign up to set email alerts
|

Resonant tunneling and Fano resonance in quantum dots with electron-phonon interaction

Abstract: We theoretically study the resonant tunneling and Fano resonance in quantum dots with electronphonon (e-ph) interaction. We examine the bias-voltage (V ) dependence of the decoherence, using Keldysh Green function method and perturbation with respect to the e-ph interaction. With optical phonons of energy ω 0 , only the elastic process takes place when eV < ω 0 , in which electrons emit and absorb phonons virtually. The process suppresses the resonant amplitude. When eV > ω 0 , the inelastic process is possibl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 36 publications
2
56
0
Order By: Relevance
“…Several studies have focused on electron conduction in a quantum dot (QD) embedded in one of the arms of an AB ring attached with normal-metal (N) leads. [1][2][3] In such a device, the differential conductance is modified by the magnetic flux penetrating the ring. The differential conductance is described by an asymmetric structure with a dip and a peak; this asymmetric line shape is called as the Fano resonance.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have focused on electron conduction in a quantum dot (QD) embedded in one of the arms of an AB ring attached with normal-metal (N) leads. [1][2][3] In such a device, the differential conductance is modified by the magnetic flux penetrating the ring. The differential conductance is described by an asymmetric structure with a dip and a peak; this asymmetric line shape is called as the Fano resonance.…”
Section: Introductionmentioning
confidence: 99%
“…In the DOS spectrum analysis, the phonon-assisted sidebands are shown to exhibit a broad and a narrow Lorentzian peaks, associated with the phonon-assisted bonding and antibonding states respectively, which are dependent strongly on the interdot coupling and interdot EPI strength. The behavior of multipeak satellites is distinguished from the previous single-peak satellites in single QD [19][20][21][22][23][24] or double QD system [26][27][28]. Furthermore, it is shown that the inelastic interference can survive both the low temperature (Kondo regime) and the high temperature.…”
Section: Discussionmentioning
confidence: 93%
“…It is very interesting to know [26] whether the presence of multiple inelastic paths can lead to additional quantum interference besides the usual Fano interference. Nevertheless, several works [25,27,28] in double QDs with respect to the EPI found that the inelastic scatting has little influence on the Fano interference and no interference phenomena is observed between the phonon-assisted channels. It is noticed that in the above considerations, they focused mainly on the localtype phonons which are irrelevant to the interdot coupling.…”
Section: Introductionmentioning
confidence: 96%
“…Thus, the phase change is continuous and very smooth. The positiondependent tunneling causes an inelastic process, which improves the decay of the oscillating QD and broadens the energy levels of the system [141].…”
Section: Coherent Phase Shiftmentioning
confidence: 99%